THE APPLICATION OF GUIDED INQUIRY LEARNING MODEL ASSISTED WITH CONSTRUCTIVISTIC WORKSHEET TO IMPROVE THE LEARNING RESULTS OF XI GRADE STUDENTS IN SMA NEGERI 13 SEMARANG - Wijayanti, Maria Sundus Retno (Unnes Science Education Journal, 2017)
This study aims to improve the learning outcomes of students of science in SMA N 13 Semarang on Thermochemistry competence and reaction rate using guided inquiry learning aided LKS. This research is a class act consisting of two cycles. Subjects were students. Data collected through observation and tests. The results showed that the use of guiding inquiry learning model aided LKS can improve student learning outcomes, covering the aspects of knowledge, attitude aspect (student activity) and skills aspects (performance practicum). Improved knowledge of students can be seen from the increase in the number of students who pass out of 27 students in the first cycle to 33 students in the second cycle of 37 students. Increased activity of students can be seen from the number of students with grades of 27 students completed the first cycle to 37 students in cycle II. Improved performance lab can be seen from the number of students to the value of the number of students 30 completed the first cycle to 35 students in the second cycle of 37 students.